Entering hyper-reality: “Resonance-In-Sight,” a mixed-reality art installation - Crolla, Kristof; Goepel, Garvin (Frontiers in Virtual Reality, 2022)
Enhanced virtual communicative technologies extend human perception in extraordinary ways that junction in detaching or augmenting its operator from physical reality. Prospects of the metaverse are progressing towards a possibly fully immersive cyberspace in which users will be entirely disconnected from their analogue physical surroundings. As we advance towards such an alternative reality, the practice-based research project discussed in this paper, titled ‘Resonance-In-Sight’, foresees and demonstrates the near-future of the metaverse to be a blended hyper-reality in which fiction and reality seamlessly blend into a ‘Mixed Reality’ (MR)-based, co-urban design environment. As digital content in such an environment creatively coexists with our physical cityscape, the research question posed by this project is how such media environment can be used as a proactive cultural educational tool to engage with and inform user audiences of otherwise challenging art-historical content. Through this demonstrator project, the article discusses and reflects on applied methods for user experience (UX) design and the development of MR mobile applications for effective mixed-reality installations. It further reports on employed ‘Simultaneous Localisation And Mapping’ (SLAM) techniques, which are essential for merging co-virtual design content in a hybrid metaverse, and concludes with an assessment of the project’s community impact from an analysis of available user data.